Internationally Mandatory Rules: Different Theories Explaining the Mechanism of their Application (Part II) - A. V. Asoskov (Московский журнал международного права, 2010)
The article examines different theories, which were proposed in Western European literature for explanation of the notion of internationally mandatory rules (art. 1192 of Russian Civil Code). The content, advantages and disadvantages of the following theories are analyzed: theory of strictly territorial application of public law rules, special connection theory, theory of the proper law of contract, theory of taking internationally mandatory rules into consideration as facts of the case, as well as theory of special multilateral conflict of law rules.The author does not recommend using different criteria in order to determine the opportunity of taking into consideration the internationally mandatory rules of lex contractus, on the one hand, and internationally mandatory rules of third states, on the other hand. The author comes to the conclusion that the most promising are the special connection theory and theory of taking internationally mandatory rules into consideration as facts of the case, as well as their combination, which means the opportunity of application of this or that internationally mandatory rule on two consecutive levels – level of international private law and substantive law level.